PERAN BAHASA DAERAH SEBAGAI IDENTITAS BUDAYA: STUDI ETNOLINGUSITIK PADA SUKU ADANG BUOM - Ayu Maro; Naomi Pulamau, Gamelia Langkamang, Putri Letde, Martha Sengaji, Ribka Maukaling, Oktovina Modu, Hale (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the role of Adang language as a cultural identity of the people of Adang Buom Village, Teluk Mutiara District, Alor Regency, East Nusa Tenggara Province. The method used is qualitative description with interview techniques with community leaders, Mr Rudi Haan. The results showed that Adang language has an important role in oral tradition, song, and literature, but faces the threat of extinction due to the dominance of Indonesian language. Preservation efforts have been made through the establishment of the Adang Language Literacy House and the publication of the Gospel of Mark Bible and Song of Songs in this language. It is hoped that the community, the younger generation, and researchers will continue to contribute in preserving and developing the Adang language so that it will survive and be passed on to future generations.